Finishing procedures in Orthodontics: dental dimensions and proportions (microesthetics) - Roberto Carlos Bodart Brandão; Larissa Bustamente Capucho Brandão (Dental Press Editora, 2013)
OBJECTIVE: The objective of the present article is to describe procedures that can be performed to achieve excellence in orthodontic treatment finishing. The content is limited to microesthetics, which comprises the concept of ideal dental dimensions and proportions (white esthetics) and its correlation with the periodontium (pink esthetics). Standards of normality are described both in their real dimensions (dental height and width), and in those effectively perceived by the observer, the virtual dimensions. METHODS: The best scientific evidence was sought in the literature to support the clinical procedures that must guide the professional to obtain maximum esthetic quality on their treatments. Therefore, it is necessary to investigate what the other specialties in Dentistry expect from Orthodontics and, specially, what they have to offer. Clinical cases will be used to illustrate the dental movement that might maximize treatment outcome and to confront the ideal standards with the current state of the art. CONCLUSION: Treatment quality is directly related to the amount of procedures implemented by the orthodontist, associated with concepts and resources from Periodontics and Dental Prosthesis. Microesthetics cannot be seen in isolation, but rather as the key to establish a pleasant smile (miniesthetics) in addition to a harmonious face (macroesthetics) and a human being with high self-esteem (hyper-esthetics).